Time course of endothelial dysfanction and atherothrombosis markers in patients with acute myocardial infarction with ST segment elevation and type 2 diabetes mellitus depending on reperfusion therapy approach - Minukhina, Diana; Babadzhan, Volodymyr; Minukhin, Dmytro; Yevtushenko, Denis; Tverezovskiy, Mihail; Kudrevych, Oleksandr (My University, 2020)
The aim: To evaluate the levels of plasminogen activator type 1 inhibitor, asymmetric dimethylarginine and endothelial nitric oxide synthase on day 10-14 in patients, depending on the presence or absence of concomitant type 2 diabetes and the type of reperfusion therapy. Materials and methods: The study involved 130 patients with acute myocardial infarction, divided into 2 groups: Group 1 consisted of patients with acute myocardial infarction with type 2 diabetes mellitus (n = 73), Group 2 comprised patients with acute type 2 diabetes mellitus (n = 57). The quantitative content of IAP-1 was determined by enzyme- linked immunosorbent assay using a commercial test system manufactured by Technoclone PAI-1 ELISA Kit (Austria), NOS – Enzyme-Linked Immunosorbent Assay (ELISA) Kit for Nitric Oxide Synthase Endothelial (NOS) ADMA ELISA Kit (Austria). Results and conclusions: Percutaneous coronary intervention contributes to a significant reduction in the content of ADMA, which is a marker of endothelial dysfunction and increase NOS on the 10-14th day of acute myocardial infarction compared with standard therapy. During PCI, the level of IAP-1 did not significantly change in the time course of treatment due to post-inflammatory and post-traumatic activation of platelets in the vascular wall.
Keywords: acute myocardial infarction; type 2 diabetes mellitus; endothelial dysfunction; asymmetric dimethylarginine; plasminogen activator inhibitor type 1; percutaneous coronary intervention (PCI)